Identifying stem cells role in ulcerative colitis by bioinformatic analyses - Ordonez Moran, P. (2024)
Stem cells play a crucial role in maintaining and repairing the intestine in adults. The intestine is a rapidly renewing tissue, and stem cells located in specific regions called crypts of Lieberkühn are responsible for replenishing damaged cells. However, in Inflammatory Bowel Disease (IBD), which is characterized by intestinal chronic inflammation, the function of these stem cells can be impaired, leading to compromised tissue repair and disruption of the intestinal barrier function. To better understand the underlying mechanisms of IBD, our research group is using cutting-edge technologies to study IBD in a controlled laboratory setting. Samples from patients with IBD and healthy volunteers are collected, including inflamed and non-inflamed areas of the intestine, and are used to grow patient-derived organoids (PDOs) that retain their stem cell properties. The objective of this bioinformatic approach is to better understand stem cell’s role and other relevant pathways in IBD. The data generated will help to identify key molecular triggers which are involved in IBD. By integrating these findings with the 3D organoid model’s data, insights will be gained into the regulation of stem cells in IBD, tissue regeneration and intestinal epithelial function. Ultimately, our findings may have clinical applications in improving treatment strategies and developing precision medicine for patients with IBD, leading to better outcomes and improved quality of life for those affected by this chronic condition.